Telaah Kurikulum Merdeka di SMA (Strategi Menyiapkan Generasi Z dalam Ekosistem Pembelajaran Digital) - Anissa Awalia Rizki; Muhammad Arifin Rahmanto; Sherril Fayza Aulia; Lismawati Lismawati (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the implementation of the Merdeka Curriculum in Indonesian senior high schools as a strategic response to the challenges of digital transformation and the learning characteristics of Generation Z. Using a qualitative library research method, the study synthesizes empirical findings, policy documents, and theoretical perspectives related to curriculum implementation, digital pedagogy, and student digital literacy. The results show that the Merdeka Curriculum is primarily implemented through project-based learning, differentiated instruction, blended learning models, and digital platforms, such as the Merdeka Mengajar Platform (PMM) and Learning Management Systems. Teachers play a crucial role as facilitators, yet many still face difficulties due to limited digital pedagogical competence, inadequate infrastructure, and gaps between policy expectations and school realities. The study also identifies key factors influencing implementation effectiveness, including supportive policy alignment, teacher TPACK mastery, technological readiness, and students’ digital literacy, particularly in critical thinking and ethical use of technology. The conclusion highlights that successful implementation requires strengthening teacher competence, improving digital facilities, and designing learning strategies aligned with Generation Z’s visual, interactive, and collaborative learning preferences. The main scientific contribution of this research lies in the development of the Integrated Digital Learning Model (IDLM), which integrates policy, pedagogy, and generational characteristics to guide more contextual and sustainable implementation of the Merdeka Curriculum within digital learning ecosystems. Keywords: Merdeka Curriculum, Digital Learning, Generation Z, TPACK Integration, Curriculum Implementation